Evaluation of Heterosis and Combining Ability for Grain Yield and Yield Attributing Traits in Bread Wheat (Triticum aestivum L.): Heterosis and Yield Dynamics in Wheat - Girishbhai, Vora Harvi; Pansuriya, Ashwin; Lunagariya, Heet; S Sri Manasa; Borkhatariya, Tejas (Journal of Cereal Research, 2025)
The experiment using half-diallel mating design was conducted at wheat research station, Junagadh Agricultural University, Junagadh. Eight lines along with 28 hybrids and one standard check (GW 547) were evaluated in randomized blocked design in Rabi, 2024-25 season to study the extent and magnitude of heterotic effects of hybrids over better parent and standard check. Also it revealed the importance of both additive as well as non-additive genetic variances for control of various traits through combining ability analysis. The analysis of variance revealed highly significant differences among the genotypes for all the characters studied, indicating that experimental materials had sufficient genetic variability for all traits. The cross DBW 187 × HD 3377 (48.58 %) depicted the highest desirable heterosis over better parent followed by CG 1036 × UP 2968 (44.92 %) and CG 1036 × MP 1358 (38.17 %). The cross GW 547 × UP 2968 (35.20 %) recorded the highest significant heterosis towards positive direction over standard check, followed by CG 1036 × UP 2968 (34.92 %) and AKAW 5104 × GW 547 (34.78 %). The ratio of additive gene action to non-additive gene action (σ2gca/ σ2 sca) indicated the predominance of non-additive gene effects for these traits. The parent GW 547 considered as best general combiner. The highest sca effects was manifested by the cross DBW 187 × HD 3377 followed by AKAW 5104 × GW 547 and CG 1036 × UP 2968. Hybrid DBW 187 × HD 3377 was also found good specific combiner for number of effective tillers per plant, length of main spike, number of spikelets per main spike, grain filling period, number of grains per main spike, 100-grain weight and biological yield per plant. Overall, recognizing and leveraging non-additive gene action offers a promising avenue for accelerating genetic gains and enhancing productivity in wheat.